IMPACT OF SPORTS AGE AND SPENT TIME WITH COACH ON COACH’S COMMUNICATION LEVELS - Osman GUMUSGUL; Utku IŞIK; Mehmet ACET; Ramazan KONAK (Sport şi Societate, 2017)
The purpose of this study was to research the impact of sports year and spent time with coach on coaches’ communication levels among the professional badminton players. In total, 66 athletes (33 female and 33 male) who were players of the different university teams during the 2015 Intercollegiate Sport Season, participated to this research. Within the scope of this study, The Coach Communication Scale (Abakay and Kuru, 2009) was applied to the participants. The Scale was applied to the participants in groups at the places they had been camping for the seasons or before group exercises. The data gathered from the participants was entered into the SPSS program (version 22.0) package and multiple linear regression was applied (p<0.05). According to statistical analysis, sports time and spending time with coach were evaluated together, there was significant correlation between the scores of communication coach (R=0.712, R2=478, p<0,05).Name the two variables together explained us the total variance of communication of the coach was approximately 48%. According to the standardized regression coefficient (β), the order of importance of predictive variables on the contact point of the coaches, sports time, in the way that time together. The significance of regression coefficients t-test results were analysed, it was observed that only the duration of the sport the coach was a significant predictive of the variable on the communication. Spending time with the coach did not have a significant effect. Consequently, the number of years they spent with their coaches for athletes did not mean that good communication was established with the coaches. It was not about the time they spent with them but it was associated with sports years. This study had a same result of which had been done by Abakay and Kuru in 2009. Thus, athletes’ establish good communication with their coaches not related their coaches’ approaches, it was probably related with their sport age and professionalism levels of the sport.